PERAN INSTRUKTUR DALAM MENINGKATKAN KOMPENTENSI PEMBUATAN POLA BUSANA DALAM PELATIHAN MENJAHIT PAKAIAN DI BBPVP SERANG - Meitadela Solehah; Dyah Permatasari; Reggy Putra Pratama Widika (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The findings reveal that instructors play multiple roles: as facilitators, motivators, guides, and evaluators. As facilitators, they create a conducive learning environment that encourages active participation and collaboration among trainees. As motivators, they inspire and build confidence, helping participants overcome challenges in mastering fashion pattern-making skills. As guides, instructors provide step-by-step direction in technical processes such as body measurement, drafting basic patterns, modifying designs, and conducting fittings. Finally, as evaluators, they assess trainees’ progress through portfolio reviews, practical examinations, and certification standards, ensuring that competencies meet the requirements of the Indonesian National Work Competency Standards (SKKNI), they provide resources and create a conducive learning environment; as motivators, they encourage participants to remain enthusiastic despite challenges; as guides, they assist trainees in mastering body measurement, drafting basic patterns manually or using CAD, modifying designs, and conducting fittings; and as evaluators, they assess participants’ work through practical tests and portfolios, offering constructive feedback. Effective instructor involvement accelerates the mastery of technical skills while fostering soft skills such as accuracy, problem solving, teamwork, and creativity. Furthermore, official certification from the National Professional Certification Agency (BNSP) ensures national recognition of competencies, preparing graduates to compete in the fashion industry or establish independent businesses. In conclusion, instructors serve as key agents in bridging theory and practice, improving vocational training quality, and supporting the growth of the creative economy in the region.